Managerial approaches and organizational mechanisms of strategic development of water management at the regional level - Zubko, Anastasia (Національний технічний університет "Харківський політехнічний інститут", 2025)
The article examines the organizational and managerial mechanisms for implementing the strategy for developing water resources in the region, in the context of decentralization, climate change, and the growth of socio-economic risks. It is substantiated that effective management of water resources at the regional level requires a combination of territorial and basin approaches, as well as coordination among the state, local governments, businesses, and the main groups of water users. The role of the organizational and managerial mechanisms as key components of the regional organizational and economic mechanism for water management, ensuring the economic, social, and environmental efficiency of water resource use, is revealed. Attention is paid to the problems of water management in the southern regions of Ukraine, amid limited water resources, the degradation and destruction of hydraulic infrastructure, and the growth of anthropogenic pressure on water ecosystems. The expediency of strengthening the role of regional management is proven, provided that the state's strategic and regulatory functions are preserved, thereby increasing the adaptability of managerial decisions to the specifics of individual territories. The creation of territorial (basin) interdepartmental bodies for water management and the development of cluster structures of water users are proposed as tools to increase the efficiencyof implementing regional development strategies. It is substantiated that the cluster approach in water management contributes to the concentration of resources, the attraction of investment, the introduction of innovative technologies, the restoration of irrigation, and the strengthening of food security in regions. The main conditions for the formation of water clusters are formulated, and their advantages, potential limitations, and operational risks are identified. The practical significance of the results lies in their possible use by state authorities and local self-government bodies to develop and implement water management strategies in the regions.

У статті досліджено організаційно-управлінські механізми реалізації стратегії розвитку водного господарства регіону в умовах децентралізації, кліматичних змін та зростання соціально-економічних ризиків. Обґрунтовано, що ефективне управління водними ресурсами на регіональному рівні потребує поєднання територіального та басейнового підходів, а також узгодження інтересів держави, органів місцевого самоврядування, бізнесу та основних груп водокористувачів. Розкрито роль організаційно-управлінського механізму як ключової складової регіонального організаційно-економічного механізму водного господарства, що забезпечує досягнення економічної, соціальної та екологічної ефективності використання водних ресурсів. Особливу увагу приділено проблемам управління водокористуванням у південних регіонах України в умовах обмеженості водних ресурсів, деградації та руйнування гідротехнічної інфраструктури, а також зростання антропогенного навантаження на водні екосистеми. Доведено доцільність посилення ролі регіонального рівня управління за умови збереження стратегічних і регуляторних функцій держави, що дозволяє підвищити адаптивність управлінських рішень до специфіки окремих територій. Запропоновано створення територіальних (басейнових) міжвідомчих органів управління водним господарством та розвиток кластерних структур водокористувачів як інструментів підвищення ефективності реалізації регіональних стратегій розвитку. Обґрунтовано, що кластерний підхід у сфері водного господарства сприяє концентрації ресурсів, залученню інвестицій, впровадженню інноваційних технологій, відновленню зрошення та зміцненню продовольчої безпеки регіонів. Сформульовано основні умови створення водогосподарських кластерів, визначено їх переваги, потенційні обмеження та ризики функціонування. Практичне значення результатів полягає у можливості їх використання органами державної влади та місцевого самоврядування при розробленні й реалізації стратегій розвитку водного господарства регіонів.
Управлінські підходи та організаційні механізми стратегічного розвитку водного господарства на регіональному рівні
Keywords: water management; regional development; organizational and managerial mechanisms; basin management; cluster; decentralization; водне господарство; регіональний розвиток; організаційно-управлінський механізм; басейнове управління; кластер; децентралізація